1996
DOI: 10.1093/glycob/6.2.165
|View full text |Cite
|
Sign up to set email alerts
|

Elongation of the N-glycans of fowl plague virus hemagglutinin expressed in Spodoptera frugiperda (Sf9) cells by coexpression of human β1,2-N-acetylglucosaminyltransferase I

Abstract: Spodoptera frugiperda (Sf9)-cells differ markedly in their protein glycosylation capacities from vertebrate cells in that they are not able to generate complex type oligosaccharide side chains. In order to improve the oligosaccharide processing properties of these cells we have used baculovirus vectors for expression of human (beta 1,2-N-acetylglucosaminyltransferase I (hGNT-I), the enzyme catalysing the crucial step in the pathway leading to complex type N-glycans in vertebrate cells. One vector (Bac/GNT) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
57
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 51 publications
1
57
0
Order By: Relevance
“…It is noteworthy that this enzyme could not hydrolyze Man5Gn, 4 but acted only further "downstream" on MGn and GnGn where it specifically removed GlcNAc-1 (20). Subsequent cell culture experiments in the presence of hex-osaminidase inhibitors (7,11,21) or of recombinant ␤1,4-galactosyltransferase (22,23) corroborated the putative existence of a processing hexosaminidase. It is obvious, therefore, that this enzyme interferes in strategies to produce glycoproteins with human-like glycosylation in insect cells.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…It is noteworthy that this enzyme could not hydrolyze Man5Gn, 4 but acted only further "downstream" on MGn and GnGn where it specifically removed GlcNAc-1 (20). Subsequent cell culture experiments in the presence of hex-osaminidase inhibitors (7,11,21) or of recombinant ␤1,4-galactosyltransferase (22,23) corroborated the putative existence of a processing hexosaminidase. It is obvious, therefore, that this enzyme interferes in strategies to produce glycoproteins with human-like glycosylation in insect cells.…”
mentioning
confidence: 77%
“…The most common substitution is the presence of terminal GlcNAc on the ␣1,3-linked mannosyl residue (GlcNAc-1) 3 added by GlcNAc-transferase I, although in a few cases further modifications such as galactose, N-acetylgalactosamine, fucose, and aminoethylphosphonate (i.e. phosphorylethanolamine) have been found linked to this GlcNAc residue (7)(8)(9)(10)(11). The occurrence of larger and sialylated N-glycans has been reviewed elsewhere (1,4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This idea led some investigators to attempt to modify the protein N-glycosylation pathway in baculovirus-infected insect cells by introducing exogenous glycosyltransferase activities into the system (for a general review, see Jarvis et al, 1998a). Wagner et al (1996b) demonstrated that the N-glycans of fowl-plague hemagglutinin expressed in Sf9 cells could be elongated by coexpression of human β1,2-Nacetylglucosaminyltransferase I (GNT-I). These authors used two different recombinant baculoviruses, one expressing the hemagglutinin and the other expressing the human GNT-I gene, to coinfect Sf9 cells.…”
Section: Engineering Glycoprotein Processing Pathways In the Baculovimentioning
confidence: 99%
“…63 Two strategies have been used to "humanize" glycan structures in insect cells; integrating the missing glycosyltransferases into either the cellular genome 83 or the viral genome. 84 Using the latter approach, we have constructed a new baculovirus expressing GNT-I, GNT-II and β1-4 galactosyltransferase (Cérutti M, et al unpublished data). In order to obtain a stable genetic construct without any duplicated sequences, we chose to direct the gene expression under the control of RNA polymerase II heterologous promoters.…”
Section: Enhancing the Production And Secretion Of Recombinant Antibomentioning
confidence: 99%